Advocacy and Rhetoric vs. Scholarship and Evidence in the Debate over Contingency Fees: A Reply to Professor Brickman - Herbert M. Kritzer (Washington University Law Quarterly, 2004)
In December 2001 I received a telephone call from a lawyer at a firm representing Baxter International, Inc. At that time, Baxter was facing lawsuits over a number of dialysis-related deaths that had occurred in Europe. Apparently dialysis filters manufactured at a Baxter plant in Sweden had been contaminated by a processing chemical resulting in adverse consequences when used with dialysis machines. Baxter had settled death claims involving ten Spanish patients who had died (for $289,000 each), but was facing claims in as many as another 40 cases. American contingency-fee lawyers had begun to contact families in Europe and the possibility of lawsuits in the United States was looming, with the prospect of damage payments far greater than roughly $300,000 per person. The lawyer who contacted me was seeking someone to whom his firm, or the firm’s client, could refer European journalists who would tell them about the problems with American contingency fees. He had in mind horror stories, including the supposed likelihood that the lawyers would end up with more of the proceeds than their clients. I told the lawyer that I would certainly be happy to speak with any journalists who contacted me, but I also asked whether the lawyer had visited my website to review my writings on contingency fees. When the lawyer indicated that he had not, I suggested that he just might want to do so, because he would probably determine that I was unlikely to say the kinds of things his firm’s client was hoping the journalists would hear. I went on to suggest that if he was looking for someone who would bad-mouth contingency fees, he might want to contact Professor Lester Brickman (“Brickman”). Brickman had established himself as the leading proponent of the view that contingency fees were a problem and that they needed to be substantially limited so that lawyers would not, supposedly, take advantage of naive clients and reap windfall fees. I do not know whether the lawyer contacted Professor Brickman or, if he did, whether the lawyer indicated that I had made the referral. Professor Brickman’s recent article in this law review suggests the kinds of things that he might have been expected to say. Regrettably, while his claims make good material for journalists, they also demonstrate his inclination to let his advocacy distort his scholarship. He also demonstrates a naiveté, perhaps resulting from a lack of training, about the norms and practices of social science. Rather than critiquing my work from within those norms, Brickman falls back on the use of anecdotes and horror stories, which while interesting, are the tools of the advocate not the social scientist.
Keywords: Contingent fees; Social science research; Lawyers' fees